Fluid Dynamic and Thermal Performance of a V-Shape Slotted Cylinder - Abdulwahab Alhashem; Sultan Alshareef; Ali Y. Alharbi; Mosab A. Alrahmani (Energies)
The flow characteristics and thermal performance of circular cylinders with V-shape slots are investigated numerically. The simulation is a two-dimensional incompressible flow that employs the semi-implicit finite volume multi-material algorithm MPM-ICE, which is a module of the Uintah framework. The normalized slot width s2/D ranges from 0.1 to 0.2, and the corresponding increases in total surface area are from ~99% to ~70%, respectively. Compared to the solid cylinder, the slotted cylinder has the largest total drag reduction of ~67% at s2/D of 0.2. Meanwhile, although the heat transfer is proportional with the surface area, the thermal performance of the V-shape slot first improves with the slot width, and then declines. The heat transfer improvement has an optimum value of ~192% at s2/D of 0.15. The overall slot performance, defined by the ratio of the heat transfer to the drag force, is best at 0.175.